Population fluctuation of jassid, and shoot and fruit borer of okra - Mohammad, A; Alam, SN; Miah, MRU; Amin, MR; Smriti, RS (Bangladesh Journal of Agricultural Research, 2019)
A field study was conducted at the research field of Entomology Division, Bangladesh Agricultural Research Institute (BARI), Gazipur during April to July, 2016 to measure the population fluctuation of jassid (Amrascabiguttulabiguttula), and shoot and fruit borer of okra (Eariasvittella). Results revealed that jassid was always found in okra leaf during the whole study period. The highest jassid population was found during June and population reduced at the last week of July. Jassid population had significant positive relationship with temperature and significant negative relationship with relative humidity and rainfall. The weather parameters contributed 63.1% abundance of jassid population. But temperature had the most important effect which contributed 31.4% population fluctuation of jassid. Okra shoot and fruit borer population was the lowest during May and the highest at the end of June. There were non-significant relationship between okra shoot and fruit borer population and weather parameters. Multiple regression equation exerted 15.2% effect of weather parameters on okra shoot and fruit borer population abundance. Bangladesh J. Agril. Res. 44(3): 493-499, September 2019